1998
DOI: 10.1073/pnas.95.21.12657
|View full text |Cite
|
Sign up to set email alerts
|

Neural systems underlying learning and representation of global motion

Abstract: A BSTR ACTWe demonstrate performance-related changes in cortical and cerebellar activity. The largest learning-dependent changes were observed in the anterior lateral cerebellum, where the extent and intensity of activation correlated inversely with psychophysical performance. After learning had occurred (a few minutes), the cerebellar activation almost disappeared; however, it was restored when the subjects were presented with a novel, untrained direction of motion for which psychophysical performance also re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
70
1
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(95 citation statements)
references
References 40 publications
18
70
1
2
Order By: Relevance
“…This result suggests that subsequent learning depended on enhanced attention to the task initially, and the reduction of activa- tion in attention-related areas during learning may represent a reduced requirement for attention as the task became easier (Vaina et al, 1998). This may also have contributed to the reduced activations within visual cortex (Kastner et al, 1998).…”
Section: Changes In Attention-related Areas During Perceptual Learningmentioning
confidence: 80%
See 2 more Smart Citations
“…This result suggests that subsequent learning depended on enhanced attention to the task initially, and the reduction of activa- tion in attention-related areas during learning may represent a reduced requirement for attention as the task became easier (Vaina et al, 1998). This may also have contributed to the reduced activations within visual cortex (Kastner et al, 1998).…”
Section: Changes In Attention-related Areas During Perceptual Learningmentioning
confidence: 80%
“…The results, when superimposed on retinotopic maps of individual subjects, revealed that the reduced activations were seen as early as V1 but mainly in V3-V4 and beyond, all of which contain populations of neurons that are sensitive to stimulus contrast (Boynton et al, 1999;Reynolds et al, 2000;Gardner et al, 2005;Lu and Roe, 2007). Previous studies reported perceptual learning effects in early visual areas, including V1 and V4, when subjects were trained on fine discriminations of simple visual features, such as orientation and texture (Schiltz et al, 1999;Schoups et al, 2001;Schwartz et al, 2002;Furmanski et al, 2004;Yang and Maunsell, 2004;Sigman et al, 2005;Raiguel et al, 2006), and in motion-sensitive areas MT and MST, when subjects were trained on motion discrimination tasks (Zohary et al, 1994;Vaina et al, 1998). These results, together with ours, suggest that learning occurs in visual areas in which the task-relevant visual information is processed.…”
Section: Changes In Visual Cortex Activation During Perceptual Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…(e.g. Zihl et al 1983;Vaina et al 1998;Tsushima et al 2006;Huxlin et al 2009;Furlan and Schwarzbach 2009) and hence we assume that groups of neurons within this area might respond to stimuli moving in a specified direction. 2 For the purpose of the simulations we considered eight groups or pools of neurons which respond when a substantial amount of dots move coherently into their preferred direction.…”
Section: General Setupmentioning
confidence: 99%
“…Ball and Sekuler 1987;Vaina et al 1998), and that this ability might even increase without an actual perception (Watanabe et al 2001). Furthermore, neuroimaging studies demonstrated that changes in cortical activations might accompany perceptual learning in general (e.g.…”
Section: Introductionmentioning
confidence: 99%